The innate immune IMD pathway is a key regulator of gut microbiome and metabolic homeostasis in the black tiger shrimp (Penaeus monodon) - Premruethai Supungul; Sureerat Tang; Tanaporn Uengwetwanit; Umaporn Uawisetwathana; Pacharaporn Angthong; Sopacha Arayamethakorn; Phimsucha Bunphimpapha; Panyisa Potibut; Waraporn Jangsutthivorawat; Virak Visudtiphole; Sage Chaiyapechara; Wanilada Rungrassamee (PLoS ONE, 2025)
The gut microbiome plays a fundamental role in host health and homeostasis, yet immune mechanisms regulating this relationship remain poorly understood in commercially important invertebrate such as the black tiger shrimp ( Penaeus monodon ). We employed a multiomics approach, combining RNA interference (RNAi) with transcriptomic, metabolomic, and 16S rRNA gene profiling, to investigate how the innate immune Toll and IMD pathways regulate gut health. We systematically suppressed key signaling components, MyD88 (Toll) and Relish (IMD), under non-pathogenic conditions. Knockdown of the IMD pathway transcription factor, Relish , triggered a profound and selective response across all measured biological layers. We observed a disproportionately large transcriptomic change, with 1,362 differentially expressed genes (DEGs) in the Relish knockdown group compared to only 333 DEGs in the MyD88 knockdown group. This was accompanied by a targeted alteration in immune effectors, including the upregulation of lysozyme C-like (log 2 fold change = 2.44) and a strong suppression of penaeidin 5 (log 2 fold change = −3.62). At the microbial level, while overall community structure remained stable, a selective shift was observed, the abundance of specific Gram-negative genera, particularly Photobacterium and Shewanella , was significantly reduced, yet Pseudoalteromonas were enriched in the Relish knockdown group. Metabolomic analysis further revealed that the Relish -suppressed shrimp had a distinct metabolic signature, marked by a decrease in bacterial-associated metabolites like D-alanyl-D-alanine and an increase in pro-inflammatory markers such as succinic acid and 8-HETE. Our findings showed that in P. monodon , the IMD pathway is the primary and central regulator of gut microbiome and metabolic homeostasis. This study provides novel insights into the dynamic interplay between innate immunity and the gut microbiome in a crustacean, identifying the IMD pathway as a promising target for developing strategies to enhance shrimp health and the sustainability of the global aquaculture industry.